TINDAK PIDANA DENGAN SENGAJA MENYEBABKAN KEBAKARAN MENGAKIBATKAN KEMATIAN DIPUTUS PASAL 359 KUHP - Fachri Ardias Setiawan; Prastopo (Reformasi Hukum Trisakti, 2022)
The defendant committed crime on February 15th, 2021 when he returned home because a headache. Arriving at the house he intended to commit suicide by setting himself on fire, but when he started the fire, he felt pain from the fire and he came out from the burning house. Remembering his mother was in the house, the defendant return, but fire had burned the house and caused his mother to burn and died. The Judges in Decision Number 76/Pid.B/2021/PN Bbs, sentenced the Defendant with criminal sentence because it was legally proven he have violated Article 359 of Criminal Code. Whether the defendant fulfilled the elements of Article 359 of Criminal Code and what types of offenses can be imposed on the defendant are the main problems. This research uses prescriptive law type, namely descriptive analytical legal research, using secondary data obtain through library research. analyzed qualitatively and conclusions drawn using deductive understanding. The conclusions: decision from the judges which found the defendant guilty of violating Article 359 of Criminal Code was inappropriate, they should be applying Article 187 paragraph (3) and (2); The defendant’s offenses including: criminal, material, commission, concrete, general, offenses causing danger, completed, single, ordinary and simple offenses.